QiMing granules for diabetic retinopathy: a systematic review and meta-analysis of randomized controlled trials - Zhang, Yazi; Shi, Menglong; Peng, Dehui; Chen, Weijie; Ma, Yucong; Song, Wenting; Wang, Yuetong; Hu, Haiyin; Ji, Zhaochen; Yang, Fengwen (Frontiers in Pharmacology, 2024)
To assess the efficacy and safety of QiMing granules (QM) in the treatment of patients with diabetic retinopathy (DR). We systematically searched multiple databases. Randomized controlled trials (RCTs) of QM in the treatment of DR were collected, and the search time limit was from the establishment of the database to March 27, 2024. Two independent researchers were involved in literature screening, data extraction, and bias risk assessment. The risk of bias in the included studies was assessed using the Risk of Bias Assessment tool for randomized controlled trials of Cochrane Collaboration 2.0 (RoB 2.0). Review Manager 5.4.1 and Stata 15.1 were used for meta-analysis. A total of 33 RCTs involving 3,042 patients were included in this study. Overall, we demonstrated that QM had a significant clinical effect on DR. QM alone was superior to conventional treatment (CT) in terms of overall efficacy [RR = 1.45, 95% CI: (1.34, 1.58), P < 0.00001, moderate certainty], retinal circulation time [MD = -0.56, 95% CI: (-1.01, -0.12), P = 0.01] and macular thickness [MD = -11.99, 95% CI: (-23.15, -0.83), P = 0.04]. QM plus CT was superior to CT in terms of overall efficacy [RR = 1.29, 95% CI: (1.24, 1.33), P < 0.00001], visual acuity [MD = 0.14, 95% CI: (0.11, 0.17), P < 0.00001], macular thickness [MD = -14.70, 95% CI: (-21.56, -7.83), P < 0.0001], TG [MD = -0.20, 95% CI: (-0.33, -0.08), P = 0.001, moderate certainty], TC [MD = -0.57, 95% CI: (-1.06, -0.07), P = 0.02], and LDL-C [MD = -0.36, 95% CI:(-0.70, -0.03), P = 0.03]. In terms of safety, the incidence of adverse events in the experimental group was less than that in the control group. The results of the GRADE evidence quality evaluation showed that the evidence quality of outcome indicators was mostly low. QM can effectively improve overall efficacy, visual acuity, macular thickness, retinal circulation time, and reduce the levels of TG, TC, and LDL-C. However, due to the limitations of this study, more multi-center and large sample studies are needed to confirm the conclusion.